Peptide mimotopes of malondialdehyde-epitopes for clinical applications in cardiovascular disease. Issue 2 (January 2015) - Amir, Shahzada; Hartvigsen, Karsten; Wagner, Oswald; Tsimikas, Sotirios; Witztum, Joseph L.; Binder, Christoph J
Abstract: Introduction: Autoantibodies specific for malondialdehyde modified LDL (MDA-LDL) represent potential biomarkers to predict cardiovascular risk. However, the generation of MDA-LDL results in the formation of many different epitopes with high variability. Because it is not known, which MDA epitope is biological important, the aim of this study was to identify and characterize peptide mimotopes of MDA-LDL that could be used as antigens to improve the reproducible detection of MDA-specific autoantibodies. Methods and Results: Peptide phage display libraries were screened for phages binding to the MDA-LDL specific natural IgM antibody LR04. After biopanning two consensus sequences (P1 & P2) of binding phages were synthesized. P1 and P2 were specifically bound by LR04, as the binding of LR04 to coated peptides was fully competed by MDA-LDL but not native LDL. P1 and P2 were also bound by other MDA specific murine (EN1) and human (IK17) antibodies. Furthermore, the binding of LR04 to late apoptotic cells was completely inhibited by both peptides, identifying them as mimotopes of naturally occurring epitopes on dying cells. Immunization of C57BL/6 mice with P2 conjugated to BSA, but not BSA alone, resulted in the robust induction of IgG1 and IgM antibodies against MDA-LDL. Moreover, serum IgG of immunized mice specifically stained epitopes in atherosclerotic lesion of rabbits and humans. Finally, we measured anti-mimotope antibody titers in serum samples previously collected from healthy subjects (n=17) and from patients (n=140) with stable angina pectoris undergoing percutaneous coronary intervention (Tsimikas, 2004). In patients a significant positive correlation was observed between anti-MDA-LDL and anti-mimotope IgM (P1, r=0.8; P2, r=0.6; p<0.0001) and IgG (P1, r=0.4; P2, r=0.3; p<0.0001) antibodies. A similar correlation was also found in sera of healthy subjects with IgM (P1, r=0.6; P2, r=0.4; p<0.0004) and IgG (P1, r=0.7; P2, r=0.5; p<0.0001) antibodies. Conclusions: Thus, we have identified specific mimotopes of MDA-LDL that serve as highly reproducible antigens to assess autoantibody titers in patients with cardiovascular disease. Future studies will reveal their usefulness for therapeutic vaccination approaches against atherosclerosis.